Bacteriophages: unlocking a new frontier in breast cancer management by defeating oncogenic bacteria - Yasmin N. Ramadan; Zainab I. Rashed; Rehab Ahmed; Hoda A. Salem; Hanan Alshareef; Eltayib Hassan Ahmad-Abakur; Fawaz E. Alanazi; Hassabelrasoul Elfadil; Helal F. Hetta (Future Journal of Pharmaceutical Sciences)
Abstract Background Breast cancer is a leading cause of mortality worldwide, and conventional treatments such as chemotherapy and radiation therapy face significant limitations including toxicity, variable efficacy, and resistance. There is a critical need for innovative strategies that offer precision targeting with fewer side effects. Main body Bacteriophages, traditionally recognized for their bacteriolytic activity against oncogenic bacteria, have recently emerged as promising tools in breast cancer management. Beyond their natural antibacterial role, engineered bacteriophages have been developed to act as vehicles for targeted gene delivery, drug delivery, and vaccine production. Phage display technologies enable the presentation of tumor-specific ligands, enhancing specificity and minimizing off-target effects. Additionally, phage-mediated targeting can modulate the tumor microenvironment and improve immune responses against breast cancer. Conclusion Bacteriophages represent a dual therapeutic strategy in breast cancer: eradication of oncogenic bacteria and precision engineering as nanocarriers for cancer therapeutics. Their unique biological properties offer a foundation for developing safer, more effective treatments that complement or even surpass conventional approaches.